Pattern Compensation of a Planar Phased Array with Centre Elements Phase Malfunctioning Using a Genetic Algorithm - Bin Saleem, Raja Aasim; Shah, Arslan Ali; Munsif, Hina; Najam, Ali Imram; Khattak, Shahid; Irfanullah (Progress in electromagnetics research. Letters, 2024)
A phase-only and amplitude-phase genetic algorithm (GA) has been investigated to restore the array pattern of a 4 x 2 planar array in the presence of centre-elements phase malfunctioning. A single and double adjacent antenna elements are considered for phase malfunctioning. The new array weights for functioning antenna elements are computed with GA to restore the value of array peak gain and sidelobe level (SLL). The simulation results, which are verified with measurements, indicated that complete recovery of array pattern without SLL constraint in the presence of malfunctioning elements was possible with the phase-only GA weights. It is shown that the uncorrected pattern can also be compensated for main beam scanning with phase-only GA weights. However, pattern compensation with SLL constraint is not possible using the phase-only GA weights. Therefore, amplitude-phase GA weights are estimated to restore the peak gain and the desired SLL simultaneously at the cost of widening the main beam. A prototype of X-band 4*2 microstrip patch array controlled through X-band phaser evaluation boards was used in the in-house anechoic chamber measurements facility to validate the full-wave HFSS simulation results.